The Antibacterial Activity of Date Syrup Polyphenols against S. aureus and E. coli - Taleb, Hajer; Maddocks, Sarah E.; Morris, R. Keith; Kanekanian, Ara D. (Frontiers in Microbiology, 2016)
The increase in antibiotic-resistant bacteria poses a threat to health care worldwide; this has resulted in a revived interest in plant products as adjunct antimicrobial agents to control pathogenic microorganisms. A major plant group used for traditional medicinal applications is Phoenix Dactylifera L, more commonly known as the date palm. Fruit of the date palm have been used customarily in the treatment of intestinal disturbances, hypertension, oedema and gastrointestinal disease, the nomadic tribes in the Middle East have been known to use traditional date syrup as an antimicrobial agent for wound healing. In some cases these ailments can be attributed to or are strongly associated with a variety of bacterial infections and inflammation. Plant-derived products such as date syrup have demonstrated antibacterial activity and can inhibit bacteria through numerous different mechanisms, which may be attributed to bioactive compounds including plant-derived phenolic molecules. Many such products derive their inherent antimicrobial activity from the presence of polyphenols, which cause oxidative damage. This investigation demonstrated that date syrup, and polyphenols extracted from date syrup, the most abundant bioactive constituent of date syrup are bacteriostatic to both Gram positive and Gram negative Escherichia coli and Staphylococcus aureus. We have further shown that the extracted polyphenols independently suppress the growth of bacteria and have observed that date syrup behaves as a prooxidant by generating hydrogen peroxide that mediates bacterial growth inhibition as a result of oxidative stress. at sub-lethal MIC concentrations date syrup demonstrated antioxidative activity by reducing hydrogen peroxide, and at lethal concentrations date syrup demonstrated prooxidant activity that inhibited the growth of E. coli and S. aureus. The high sugar content naturally present in date syrup did not significantly contribute to this effect. These findings highlight that date syrup’s antimicrobial activity is mediated through hydrogen peroxide generation in inducing oxidative stress in bacteria.